Analysing Viewpoints Of Parents Regarding Marriage Of Their Sons And Daughters With Intellectual Disabilities In The City Of Jeddah, Kingdom Of Saudi Arabia - Alzahrani, Nasser (International Journal of Psychosocial Rehabilitation, 2024)
This study aims to analyse the views of parents of persons with Intellectual Disability about the marriage of their children in the Saudi society. This study was applied in the city of Jeddah in the Kingdom of Saudi Arabia due to the cultural diversity there and the different community customs and traditions. The study used data collected from 30 parents. This sample was randomly selected from different neighbourhoods in Jeddah. The research uses a quantitative survey questionnaire to analyse the views of parents. The study sample included a number of parents of persons with Intellectual Disabilities both males and females. Perspectives were analysed on marriage of persons with Intellectual Disabilities, the source of concern about their marriages and the potential impact of marriage on his mental and emotional state. The results of the research show that parents adhere to the views that their sons and daughters with Intellectual Disabilities should marry. However, there is a need for more studies and research on the subject of marriage for people with special needs from other categories such as people with visual impairments , Hearing disability and people with autism disorders from the feasibility of marriage for people with special needs and its psychological, moral and social impact on them.